The Design of a Noise Detection Automatisation Tool in Library – Based on Internet of Things - Dhiya, Dhiya Alfiyyah Ansar; Yuyun; Taufik, Imran (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2022)
The development of the times and technology produces innovations that facilitate human activities, one of which is for librarians to control and maintain library rooms. This study aimed to implement a noise detection automation tool and a sound monitoring system based on the Arduino nano 33 BLE sense microcontroller in a library room. The Arduino processed the data from the sound sensor through the Edge Impulse platform. Suppose a sound with a value exceeds 0.6 and takes more than 10 seconds. In that case, the warning